Analysis of Function of Tact Maxim in the Event of Marhata Sinamot Speech of Batak Toba Traditional Weddings - Nasution, Muhammad Muslim; Fahlevi, Sahrizal; Siregar, Isrina; Izar, Julisah (International Journal of English and Applied Linguistics (IJEAL), 2024)
This research aimed to describe the tact maxim in the event of Marhata sinamot of Batak Toba tradition that reviewed its function namely assertive, directive, commissive, expressive and declarative. This research used a qualitative descriptive approach; the data collection technique involved interviewing and recording, while the analysis data was described, and conclusions were made. The result showed that the tact maxim is one of the principles of politeness whose form of speech prioritizes the benefits of others and reduces/maximizes one's own benefits. From the results obtained, there are (2) assertive utterances, (10) directive utterances, (1) commissive utterances, (3) expressive utterances, and (1) declarative utterances. The dominant tact maxim based on its function was found in the directive speech act.